CTNI-32. CASE SERIES OF BRAF INHIBITORS FOR THE TREATMENT OF BRAFV600E GLIOBLASTOMA. (12th November 2021) - Wagle, Naveed; Carrillo, Jose; Sharma, Akanksha; Nguyen, Minhdan; Truong, Judy; Chow, Jared; Landa, Evie; Heng, Annie; Gill, Jaya; Barkhoudarian, Garni; Kelly, Daniel; Kesari, Santosh
Abstract: Glioblastoma is the most common and aggressive primary brain tumor. Beyond upfront therapy with radiation and temozolomide chemotherapy there is no standard therapy that has been effective. Inhibitors of BRAF and MEK, a downstream protein immediately following BRAF, have been shown to have survival benefit for patients with other BRAF V600E mutant neoplasm including advanced melanoma. We describe our experience using this combined target therapy for two patients with BRAF V600E mutant glioblastoma. Two adult patients with pathologically diagnosed glioblastoma presented with radiographic evidence of tumor progression after prior treatment with chemotherapy or immunotherapy. Neither had received radiation therapy within 3 months of starting treatment. Molecular characterization was performed though Caris which showed evidence of BRAF V600E mutation. BRAF inhibitors were initiated in combination with standard therapy options. MRI imaging was obtained to monitor for disease progression. BRAF inhibitors were tolerated well without any side effects not previously reported. Partial objective response was seen in both patients on subsequent MRI imaging within 8 weeks of starting treatment. Progression free survival and overall survival have not been reached in either case. BRAF inhibition may have therapeutic benefit in BRAF mutated glioblastoma. Partial response was seen in this case series. The molecular profile of glioblastoma may suggest treatment options beyond standard chemotherapy options. This series supports the use of BRAF inhibitors for the treatment of BRAF V600E glioblastoma A controlled trial should be supported.